ADVANCED NASOPHARYNGEAL CARCINOMA WITH NASAL POLYP: A MISDIAGNOSED CASE - Oke Kadarullah (TALENTA PUBLISHER, 2019)
Introduction: Nasopharyngeal carcinoma (NPC) commonly misdiagnosed in early stage, because of it’s multiple nonspesific sign and symptoms also because of the difficult anatomic site. Especially if there is a comorbid in the area around the nasopharynx, most likely will end up with missdiagnosis. So the mortality rate are still high due to advanced stage incidence. Case report: Reported a 58 years male with history of recurrent nasal bleeding since 6 months ago accompanied by hearing problem and also ear fullnes since 11 months ago. There also a severe headache since 4 months ago and a left neck mass arised within 2 months approximately 6 cm in dimension. In nasopharyngocopy found a gelatinous mass at right nasal cavity and nasopharyngeal mass extend to both nasal cavity. The biopsy results are polip nasi Hellquist Type I and Nonkeratinizing Carcinoma Undifferentiated type. CT showed the nasopharyngeal mass has extend intracranially. Patient’s management were planned to polypectomy and chemoiiradiation. Despite of the tumor was radiosensitive, the prognosis and the survival rate are low because the patient came at stage IV. Conclusion: Educating the society, health workers and hospital staff is a critical step for controlling NPC at early stage